2012
DOI: 10.1007/s10450-012-9449-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes as potential material for drug delivery—experiment and simulation

Abstract: We discuss the factors influencing the properties of new drug delivery system, composed of carbon nanotubes and analgesic antipyretic drug-paracetamol. Basing on experimental data it is shown, that by a simple manipulation with the heating time at the stage of system preparation, one can easily change the rate of the drug delivery. Moreover, this rate can be changed in a very wide range. Finally, using Molecular Dynamics simulation we also discuss the orientation and properties of drug molecules at different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The flat curves show a weak interaction at lower temperatures and in EtOH. The observed event was well supported by the previous studies, where the probability was found to increase exponentially as a function of the distance from the two ends of the CNT after encapsulation [30]. Note that a symmetric distribution of the g(r) plot is expected if the sampling size is large enough, with a long enough simulation time.…”
Section: System Equilibrationsupporting
confidence: 88%
“…The flat curves show a weak interaction at lower temperatures and in EtOH. The observed event was well supported by the previous studies, where the probability was found to increase exponentially as a function of the distance from the two ends of the CNT after encapsulation [30]. Note that a symmetric distribution of the g(r) plot is expected if the sampling size is large enough, with a long enough simulation time.…”
Section: System Equilibrationsupporting
confidence: 88%
“…In our previous study it was shown, for the first time, that carbon nanotubes can be successfully applied in the drug HMDD procedure [14,15]. The first results of paracetamol, (analgesic and antipyretic drug) deposition on carbon nanotubes have been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study it was shown, for the first time, that carbon nanotubes can be successfully applied in the drug HMDD procedure [14,15]. The first results of paracetamol, (analgesic and antipyretic drug) deposition on carbon nanotubes have been reported [14,15]. Paracetamol, existing in three polymorphic forms (Forms I-III having different stability and melting point), is a suitable model drug for evaluating the capacity of the extruded formulation for drug stability improvement [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Using the MD and QSPR techniques, the encapsulation of 20 antitumor drugs within carbon nanotubes have been studied. These drugs have been chosen according to the previous experimental and theoretical works . In this study, we have concentrated on the analyses of the optimal CNT size for 20 different drugs for which encapsulation can occur.…”
Section: Discussionmentioning
confidence: 99%
“…A new route has been opened in the encapsulation of drugs inside carbon nanotubes (CNTs) to change the CNTs’ properties . Researchers and manufacturing companies have considered the interesting properties of nanotubes and used them in several fields, such as new alternative and efficient tools for transporting therapeutic molecules . They have shown that drugs can be released by the CNTs into the target cells without damaging the healthy cells of the tissue.…”
Section: Introductionmentioning
confidence: 99%